Laparoscopic Sigmoid Colectomy for a Patient With Sigmoid Colon Cancer and Crossed-Fused Renal Ectopia: A Case Report - Nakai, Nozomu (Int Surg, 2015)
Crossed-fused renal ectopia (CFRE) is a very rare congenital renal malformation. This condition comprises several anatomic anomalies, including unilateral ureteral intersection of the midline, anteriorly-placed renal pelvises, and aberrant renal blood vessels, all of which increase the difficulty of colectomy. This report describes a case of laparoscopic sigmoidectomy with sufficient lymphadenectomy for a patient with sigmoid colon cancer and left-sided L-shaped CFRE. Preoperative computed tomography demonstrated that the origin of the inferior mesenteric artery (IMA) was free from anomalies and that the tumor did not invade surrounding organs. Therefore, we planned conventional laparoscopic sigmoid colectomy with D3 lymphadenectomy. Division of IMA at its origin and anterior colon resection was successfully performed by careful mobilization of the mesocolon to avoid exposing the retroperitoneal organs. To our knowledge, this is the first case report of laparoscopic colectomy for a patient with CFRE. Sufficient preoperative assessment of anatomic anomalies enabled successful surgery.